O MOVIMENTO ESTUDANTIL NA UNIVERSIDADE ESTADUAL DE PONTA GROSSA-Pr: 1969-2009 - Miyahara, Heloísa Sayumi (2011)
This research aims to rescue the historical of the student movement in UEPG (1969-2009). For this study were collected though exploratory information that led us, among other information, to research subjects. From this first approach we try to list some of the constituent elements of social movements in the beacons on the analysis of the student movement in UEPG along the junctures. Through qualitative research, conducted interviews with 11 subjects whose speech comprised the dialogue between national contexts and their relationship with the student movement (specifically the UEPG). This relationship also allowed evidence of the crucial components that characterize the ME-UEPG over the periods. Thus, we see that in the historical analysis, the student movement of UEPG not limited – in general – the representative organizations. Assuming a cyclic action, ie there are periods where the demand “require” a higher activity of groups and leaders, who make up the movement which in turn articulate their bases, revising its practices and participate in the process of fighting for improved conditions of university and/or society as a whole.